2014
DOI: 10.1074/jbc.m113.518662
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitination Regulates Expression of the Serine/Arginine-rich Splicing Factor 1 (SRSF1) in Normal and Systemic Lupus Erythematosus (SLE) T Cells

Abstract: Background:Mechanisms that control expression of the splicing factor SRSF1 in human T cells are unknown. Results: Ubiquitination and proteasome degradation of SRSF1 occur during T cell activation and in T cells from patients with systemic lupus erythematosus (SLE). Conclusion: Ubiquitin-proteasome degradation regulates SRSF1 expression in human T cells. Significance: Understanding how SRSF1 expression is regulated in SLE may enable new therapeutic approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 39 publications
(39 reference statements)
4
24
0
Order By: Relevance
“…Such an observation was not anticipated but the proteasome is one of the many interconnected protein machinery, such as chromatin remodelers, transcription factors and the RNA polymerase, that together play important roles in regulatory processes (Komili and Silver, 2008). Our observation can also be related to previous studies that indicated an interconnection between 26S proteasome and the spliceosome machinery (Bellare et al, 2008;Bieler et al, 2012), including splicing factors such as SR proteins and hnRNPs (Koumbadinga et al, 2015;Moulton et al, 2014). To our knowledge, this is the first study highlighting modulation of IKBKAP mRNA alternative splicing and IKAP/hELP1 expression levels by proteasome inhibitors in FD pathology.…”
Section: Discussionsupporting
confidence: 60%
“…Such an observation was not anticipated but the proteasome is one of the many interconnected protein machinery, such as chromatin remodelers, transcription factors and the RNA polymerase, that together play important roles in regulatory processes (Komili and Silver, 2008). Our observation can also be related to previous studies that indicated an interconnection between 26S proteasome and the spliceosome machinery (Bellare et al, 2008;Bieler et al, 2012), including splicing factors such as SR proteins and hnRNPs (Koumbadinga et al, 2015;Moulton et al, 2014). To our knowledge, this is the first study highlighting modulation of IKBKAP mRNA alternative splicing and IKAP/hELP1 expression levels by proteasome inhibitors in FD pathology.…”
Section: Discussionsupporting
confidence: 60%
“…However, more and more evidence indicate that this modification is also common to many other proteins of diverse functions in cells [14], including splicing factors [8]. Control of alternative splicing and/or splicing factors by protein degradation or ubiquitination has been observed as well [9][10][11]16,17]. Moreover, crosstalk between the acetylation and ubiquitination pathways controls important cellular proteins such as p53 through competition for the posttranslational modification of particular lysines (K Ac/Ub ) [18,19].…”
Section: Introductionmentioning
confidence: 96%
“…Of the protein modifications in cell signaling pathways, acetylation and ubiquitination each has recently been found to regulate splicing [8][9][10][11][12][13][14][15][16]. In these studies, acetylation/deacetylation effect on alternative splicing has been examined mostly from the point of histone modifications coupled with chromatin remodeling and transcription.…”
Section: Introductionmentioning
confidence: 99%
“…At the protein level, increased ubiquitination and protein degradation of CD3ζ chain was observed in T cells from SLE patients [ 33 ]. Interestingly, SRSF1 undergoes ubiquitination and proteasome degradation during normal T cell activation, and exhibits increased ubiquitination in T cells from SLE patients compared with healthy individuals [ 34 ]. Our finding of a direct correlation between the protein expression of SRSF1 and CD3ζ in SLE T cells ( Fig 1 ) not only reflects the SRSF1 mediated regulation of CD3ζ , but also common regulatory mechanisms that may be dysregulated in SLE.…”
Section: Discussionmentioning
confidence: 99%